A qualitative study exploring the factors that influence the uptake of pre‐pregnancy care among women with Type 2 diabetes. Issue 6 (4th July 2019) - Forde, R.; Collin, J.; Brackenridge, A.; Chamley, M.; Hunt, K.; Forbes, A.
Abstract: Aim: To elicit the views and experiences of women with Type 2 diabetes and healthcare professionals relating to the pregnancy and pre‐pregnancy care they have received or provided. Methods: A qualitative study using in‐depth semi‐structured interviews with women with Type 2 diabetes ( n =30) and healthcare professionals ( n =22) from primary and specialist care. Women were purposively sampled to include different experiences of pregnancy and pre‐pregnancy care. Data were transcribed verbatim and analysed thematically using Framework Analysis. Results: The median age of the women was 37 years, and most were obese (median BMI 34.9 kg/m 2 ), of black or Asian ethnicity ( n =24, 80%) and from areas of high deprivation ( n =21, 70%). Participating healthcare professionals were from primary ( n =14), intermediate ( n =4) and secondary ( n =4) care. Seven themes expressing factors that mediate reproductive behaviour and care in women with Type 2 diabetes were identified at the patient, professional and system levels. Type 2 diabetes was generally perceived negatively by the women and the healthcare professionals. There was a lack of awareness about the pre‐pregnancy care needs for this population, and communication between both groups was unhelpful in eliciting the reproductive intentions of these women. The themes also reveal a lack of systemic processes to incorporate pre‐pregnancy care into the care of women with Type 2 diabetes, and consequently, health professionals in primary care have limited capacity to provide such support. Conclusion: If the current high levels of unprepared pregnancies in women with Type 2 diabetes are to be reduced, the reproductive healthcare needs of this group need to be embedded into their mainstream diabetes management. What's new?: In the UK, 90% of pregnant women with Type 2 diabetes are not adequately prepared for pregnancy, in accordance with current guidelines. This study shows that the understanding and beliefs of women mediate their reproductive behaviours, that healthcare professionals, particularly in primary care, do not routinely engage women with Type 2 diabetes in meaningful conversations about pregnancy, and that current care systems fail to promote pre‐pregnancy care. Awareness of pregnancy preparation in the context of diabetes needs to be embedded in routine Type 2 diabetes management for women of reproductive age, underpinned by education for women and health professionals and enhanced healthcare systems.